المنهج الماركسي في الايدولوجيا: ماركس وهيغل (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research deals with the concept of ideology and how it is conceptualized by many Marxist and non- Marxist theorists, including Marxist and Hegelian intellectuals, such as: Karl Marx, Hegel, Luis Althusser, Peter B. Armitage and Raymond Williams. The research tackles the reasons which motivate the ideological institutions in Western societies to conceptualize the types of ideology in a way which suits their cultural identities and their political and intellectual biases in addition to the ideologues' trends. The result of this research is to prove that ideologies cannot be separated from politics, economics, dogmas and the State's pragmatic institutions. These ideologies are the output of an unconscious tradition imposed by these institutions on their individuals. يعالج البحث مفهوم الايدولوجيا لدى العديد من المنظرين الماركسيين وغير الماركسيين, بما فيهم أتباع ماركس وهيغل, أمثال ّّّّّّالتسير, هيغل ,بيتر ارمتاج وريموند وليامز وكارل مـاركس. كما يتطرق البحث إلى شرح واف عن نظريات وآراء هؤلاء المفكريـن والفلاسفة حول الايدولوجيا ومنطلقاتها ومبررات وجودها وخاصة تلك الايدولوجيا ت التي تتعلق بالسياسة, والمرأة, والدين, والتعليم ,ونظريات الآداب.  كما يعالج البحث الأسباب التي تدفع المؤسسات الأيديولوجية في المجتمعات المختلفة في الغرب لصياغة تلك الأنماط من الايدولوجيات, وذلك حسب ما يتناسب مع هويتها الثقافية, واتجاهاتها الفكرية والعقائـدية, والسياسية,وأهواء منّظّروا هذه الايدولوجيا ت. يخلص البحث إلى حقيقة مفادها أن الايدولوجيا لا يمكن فصلها عن السياسة والعقيدة, ومؤسسات الدولة البراغماتيه, وهي في غالب الأحيان ممارسه لاواعية لمجموع الإفراد, والمؤسسات الثقافية, والدينية, والاجتماعية, لأنها حصيلة إرث لاواعي تفرضه هذه المؤسسات على أفرادها, وهم في غالب الأحيان غير قادرين على اختيار ايدولوجيا بعينها.